Pelatihan Pengolahan Makanan Bergizi Dari Bahan Lokal Sebagai Upaya Peningkatan Gizi Keluarga - Devin Devin (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Nutrition remains a major public health challenge in Indonesia. Poor public understanding of how to select nutritious food and the lack of skills in preparing healthy food contribute to the high incidence of stunting, anemia, and other nutritional problems. This community service program aims to improve the knowledge and skills of housewives in preparing nutritious food using local ingredients. The program includes balanced nutrition counseling, cooking demonstrations, hands-on training, and assistance in preparing family menus. Results showed a significant increase in participants' knowledge of balanced nutrition and healthy cooking techniques. Participants were also able to process various local ingredients into attractive and nutritious menus. This program is expected to contribute to improving family consumption patterns and preventing nutritional problems in the community on a sustainable basis.